Metaproteomic Profile of the Colonic Luminal Microbiota From Patients With Colon Cancer - Tanca, Alessandro; Abbondio, Marcello; Fiorito, Giovanni; Pira, Giovanna; Sau, Rosangela; Manca, Alessandra; Muroni, Maria Rosaria; Porcu, Alberto; Scanu, Antonio Mario; Cossu-Rocca, Paolo; De Miglio, Maria Rosaria; Uzzau, Sergio (Frontiers in Microbiology, 2022)
Recent studies have provided evidence of interactions among the gut microbiota, local host immune cells and intestinal tissues in colon carcinogenesis. However, little is known regarding the functions exerted by the intestinal microbiota in colon cancer, particularly with respect to tumor clinical classification and lymphocyte infiltration. In addition, stool, usually employed as proxy of the gut microbiota, cannot fully represent the original complexity of colon cancer microenvironment. Here, we present a pilot study aimed at characterizing the metaproteome of tumor-associated colonic luminal contents and identifying its possible associations with cancer clinicopathological features. Colonic luminal contents were collected in operatory room from 24 colon cancer tissue specimens. After protein extraction and digestion, peptides were analyzed by liquid chromatography-high resolution tandem mass spectrometry. Mass spectra were subjected to bioinformatic analysis for database identification, label-free quantification, and taxonomic/functional annotation. Almost 30,000 microbial peptides were quantified in the samples, enabling the achievement of the taxonomic and functional profile of the tumor-associated colonic luminal metaproteome. Samples were then aggregated based on the tumor clinicopathologic variables (namely, stage, grade, and tumor-infiltrating lymphocytes) and peptide sets enabling discrimination of sample groups were identified through discriminant analysis. Several taxa showed a significant enrichment in specific groups; in particular, Bifidobacterium and Bacteroides fragilis were associated to high-stage and high-grade tumors, respectively. Among metabolic functions, formate--tetrahydrofolate ligase resulted significantly enriched in the metaproteome associated to high-stage cancer tissues. Finally, based on the results of this pilot study, we assessed the optimal sample size for differential metaproteomic studies when using colonic luminal contents as samples. In conclusion, we provide a detailed picture of the microbial and host components of the colonic luminal proteome. Moreover, we found promising associations between microbial taxa and functions and colon cancer clinicopathological features. Future studies will be needed to verify the prognostic value of these data and to fully exploit the potential of metaproteomics in enhancing our knowledge concerning colon cancer progression.